2021
DOI: 10.18502/cmm.7.1.6246
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fungal diseases in Africa: A review of diagnostic drivers

Abstract: Background and Purpose: There has been a significant increase in the burden of fungal diseases in the last few decades which has imposed a global threat to the health of humans, animals, and plants. Epidemiology of fungal diseases is not completely understood in Africa. Most of these diseases are under-reported or not reported at all mainly due to the challenges related to the availability of and access to fungal diagnostics and the lack of human resources in clinical and diagnostic mycology across the contine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…HIV-associated fungal diseases represent one of the greatest challenges in Africa. Diseases such as cryptococcosis, candidiasis, histoplasmosis, and emergomycosis are among Africa’s most affected HIV-associated diseases despite the implementation of antiretroviral therapy [ 135 ]. Recent data published by UNAIDS showed that among the 37.7 million people living with HIV worldwide, more than 25 million live in Africa [ 136 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…HIV-associated fungal diseases represent one of the greatest challenges in Africa. Diseases such as cryptococcosis, candidiasis, histoplasmosis, and emergomycosis are among Africa’s most affected HIV-associated diseases despite the implementation of antiretroviral therapy [ 135 ]. Recent data published by UNAIDS showed that among the 37.7 million people living with HIV worldwide, more than 25 million live in Africa [ 136 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Human fungal infections of the CNS are an underrepresented group of invasive infections within the African population, occurring as opportunistic infections particularly in individuals living with HIV. The most common CNS infections reported in Africa are CM and histoplasmosis (12,13). It was estimated in 2017 that ~160,000 people were diagnosed with CM in Africa, with 98% of these cases localised to the sub-Saharan region (1).…”
Section: Epidemiology Of Cns Fungal Infections In Africamentioning
confidence: 99%
“…Every year, over 2 million people die of fungal disease worldwide and many have significant morbidity from dermatophytosis, vulvovaginal candidiasis, allergic diseases, subcutaneous infections and life‐threatening invasive systemic diseases 6 . Fungal infections are common in Africa, mainly driven by HIV/AIDS, tuberculosis, poverty and the increasing number of patients with non‐communicable diseases notably, cancers, asthma and diabetes mellitus 7 . Definitive diagnosis of the fungal disease requires expertise as well as laboratory systems and equipment such as microscopy, culture, histopathology, antigen and antibody assays, and Pneumocystis PCR.…”
Section: Introductionmentioning
confidence: 99%
“…6 Fungal infections are common in Africa, mainly driven by HIV/AIDS, tuberculosis, poverty and the increasing number of patients with non-communicable diseases notably, cancers, asthma and diabetes mellitus. 7 Definitive diagnosis of the fungal disease requires expertise as well as laboratory systems and equipment such as microscopy, culture, histopathology, antigen and antibody assays, and Pneumocystis PCR. There is a scarcity of data related to fungal disease in Eritrea although reports of Eritrean migrants who have fungal infections have been published in Europe.…”
mentioning
confidence: 99%